Catalytic Action of Homeopathic Remedies for Appetite Stimulation (Homoeopathy for All, 2024)
Appetite is a vital indicator of  overall health, reflecting the body's  efficiency in utilizing nutrients. A  healthy appetite signifies proper  bodily function, while a lack of  appetite can signal various health  issues. A balanced appetite ensures  essential nutrient intake, reflecting  internal harmony and readiness  for engagement. Controlled by  hormonal, neural, and psychological  factors, appetite regulation  involves hormones like ghrelin and  leptin1, alongside insulin2, with  the hypothalamus and brainstem  integrating these signals for energy  balance.
Keywords: monitoring; Hahnemann; homeopathic